1970
DOI: 10.1007/bf02312740
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the dorsomedial hypothalamic nucleus in the “feeding center” and water intake circuitry of the weanling rat

Abstract: SummaryPrecise electrolytic lesions were placed in the dorsomedial (DMNL) and ventromedial (VMNL) hypothalamic nuclei of weanling rats to study the effect on food and water intake, body weight and length and body composition. Lesions in the DMN consistently resulted in hypophagia, hypodipsi~t and decreased ponderal and linear growth, both when compared with VMNL rats and with sham-operated controls. The DMNL rats contained more carcass water and lean body mass but less fat than the VMNL rats. The lesion effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Animals with DMNL showed hypophagia. Several studies have suggested that this nucleus underlies the neural signaling of satiety factors (31,32). For instance, 24-h food deprivation increased NPY mRNA specifically in the DMN in Otsuka Long-Evans Tokushima fatty rats, a hyperphagic and obese model, due to lack of CCK-A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with DMNL showed hypophagia. Several studies have suggested that this nucleus underlies the neural signaling of satiety factors (31,32). For instance, 24-h food deprivation increased NPY mRNA specifically in the DMN in Otsuka Long-Evans Tokushima fatty rats, a hyperphagic and obese model, due to lack of CCK-A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Stainless steel wires, 0.25 mm in diameter, telescoped into 24-gauge hypodermic needles and spar varnish-coated except for about 0.2 mm at the tip, served as electrodes. The coordinates have been previously established [Bernardis and Skelton, 1965;Bernardis, 1970a]. The rats were divided into 3 groups: group 1 received lesions in the ventromedial hypothalamus (VMH), group 2 received lesions in the Belli nger/Bernardis/M endel dorsoniedial hypothalamus (DMH) and group 3 consisted of sham-operated controls with the electrode inserted into either the VMH or DMH, but without current flow.…”
Section: Methodsmentioning
confidence: 99%
“…Only food intake and body weight gains were depressed, and then only when DMN lesions were produced prior to the placement of the VMN lesions . These data indicate that the primary changes in the weanling rat VMN syndrome, once established, cannot be significantly altered by DMN lesions which by themselves decrease food intake and ponderal and linear growth (Bernardis, 1970a;Bernardis, 1970b;Bernardis and Frohman, 1971;Bernardis, 1973a). The failure of DMN lesions to attenuate the VMN syndrome is the more striking since extensive intermingling of fibers between the VMNand DMN has been reported to exist (Chi, 1970; Millhouse, 1969; Szentagothai et al, 1968).…”
mentioning
confidence: 72%
“…These data then do not support the hypothesis that pathways between the VMN and the lateral hypothalamic area are involved in the etiology of the weanling rat VMN syndrome (Schnatz et al, 1973). However, it is possible that sympathetic pathways might be involved, traveling in the dorsal longitudinal fasciculus of Schutz and connecting the VMN with the mesencephalon and autonomic centers in the neuraxis (Arees and Mayer, 1967;Ban, 1966;Krieg, 1932).Lesions primarily destroying the dorsomedial hypothalamic nuclei (DMN) of the weanling rat caused hypophagia and reduced ponderal and linear growth in the face of normal plasma glucose, insulin, growth hormone, and lipid levels (Bernardis, 1970a;Bernardis and Frohman, 1971;Bernardis, 1973a). For review see Bernardis (1975).…”
mentioning
confidence: 98%